A systematic review and meta-analysis of randomized controlled trials of adjunctive ketamine in electroconvulsive therapy: Efficacy and tolerability. (March 2015) - McGirr, Alexander; Berlim, Marcelo T.; Bond, David J.; Neufeld, Nicholas H.; Chan, Peter Y.; Yatham, Lakshmi N.; Lam, Raymond W.
Abstract: Background: Electroconvulsive therapy (ECT) remains one of the most effective tools in the psychiatric treatment armamentarium, particularly for refractory depression. Yet, there remains a subset of patients who do not respond to ECT or for whom clinically adequate seizures cannot be elicited, for whom ketamine has emerged as a putative augmentation agent. Methods: We searched EMBASE, PsycINFO, CENTRAL, and MEDLINE from 1962 to April 2014 to identify randomized controlled trials evaluating ketamine in ECT (PROSPERO #CRD42014009035). Clinical remission, response, and change in depressive symptom scores were extracted by two independent raters. Adverse events were recorded. Drop-outs were assessed as a proxy for acceptability. Meta-analyses employed a random effects model. Results: Data were synthesized from 5 RCTs, representing a total of 182 patients with major depressive episodes (n = 165 Major Depressive Disorder, n = 17 Bipolar Disorder). ECT with ketamine augmentation was not associated with higher rates of clinical remission (Risk Difference (RD) = 0.00; 95%CI = −0.08 to 0.10), response (RD = −0.01; 95%CI = −0.11 to 0.08), or improvements in depressive symptoms (SMD = 0.38; 95%CI = −0.41 to 1.17). Ketamine augmentation was associated with higher rates of confusion/disorientation/prolonged delirium (OR = 6.59, 95%CI: 1.28–33.82, NNH = 3), but not agitation, hypertension or affective switches. Conclusion: Our meta-analysis of randomized controlled trials of ketamine augmentation in the ECT setting suggests a lack of clinical efficacy, and an increased likelihood of confusion. Individuals for whom adequate seizures or therapeutic response cannot be obtained have not been studied using randomized controlled designs. Additional research is required to address the role of ketamine in this population. Highlights: Adjunctive ketamine in the ECT setting results in longer seizures. Adjunctive ketamine in the ECT setting is not associated with higher rates of remission or response. Adjunctive ketamine in the ECT setting is associated with higher rates of delirium and confusion.